2017
DOI: 10.1021/acs.jmedchem.7b00369
|View full text |Cite
|
Sign up to set email alerts
|

New Inhibitor Targeting Signal Transducer and Activator of Transcription 5 (STAT5) Signaling in Myeloid Leukemias

Abstract: Signal transducers and activators of transcription 5 (STAT5s) are crucial effectors of tyrosine kinase oncogenes in myeloid leukemias. Inhibition of STAT5 would contribute to reducing the survival of leukemic cells and also tackling their chemoresistance. In a first screening experiment, we identified hit 13 as able to inhibit STAT5 phosphorylation and leukemic cell growth. The synthesis of 18 analogues of 13 allowed us to identify one compound, 17f, as having the most potent antileukemic effect. 17f inhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 48 publications
(136 reference statements)
1
21
0
Order By: Relevance
“…Intracellular physiological concentrations of formaldehyde also emphasize the viability of this molecule as a STAT inhibitor and the utility of bio-catalytic Mannich reactions [105]. A study by Juen et al reported the optimization of the STAT5 inhibitor, Cpd17f (Figure 3v) [103]. Interestingly, the initial hit was originally intended for PPARα/γ inhibition, while the inhibition of STAT5 phosphorylation was an off-target effect [106].…”
Section: Stat5 Inhibitorsmentioning
confidence: 99%
“…Intracellular physiological concentrations of formaldehyde also emphasize the viability of this molecule as a STAT inhibitor and the utility of bio-catalytic Mannich reactions [105]. A study by Juen et al reported the optimization of the STAT5 inhibitor, Cpd17f (Figure 3v) [103]. Interestingly, the initial hit was originally intended for PPARα/γ inhibition, while the inhibition of STAT5 phosphorylation was an off-target effect [106].…”
Section: Stat5 Inhibitorsmentioning
confidence: 99%
“…This compound is composed of a 3‐pyridinyl substituted 4,4‐dimethyl‐1,2,3,4‐tetrahydroquinoline (THQ) and indole rings, linked by an ethoxy chain attached by carbon C‐5 of the indole and nitrogen N‐1 of the THQ (Figure 1). We showed that 17 f suppressed P−Y‐STAT5 and growth of CML and AML cells [41] . We also demonstrated that 17 f sensitizes leukemic cells that acquired resistance to IM or Ara‐C [42] …”
Section: Introductionmentioning
confidence: 63%
“…Compounds 8 b and 8 c subsequently yielded 9 b and 9 c after Suzuki coupling using 2‐bromopyridine [43,44] . Concerning compound 9 b , this optimized procedure allowed us to improve the yield from 24 to 60 % in two steps [41] . Though, concerning pinacol boronate ester 8 a , coupling was not observed, surely due to steric hindrance between methyl groups of both pinacol boronate and THQ.…”
Section: Chemistrymentioning
confidence: 95%
See 2 more Smart Citations